2002
DOI: 10.1006/viro.2001.1258
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Activities for mRNA Synthesis Accompanies Loss of λ2 Spikes from Reovirus Cores: An Effect of λ2 on λ1 Shell Structure

Abstract: The 144-kDa lambda2 protein, a component of the transcriptionally active reovirus core particle, catalyzes the last three enzymatic activities for formation of the 5' cap 1 structure on the viral plus-strand transcripts. Limited evidence suggests it may also play a role in transcription per se. Particle-associated lambda2 forms pentameric turrets ("spikes") around the fivefold axes of the icosahedral core. To address the requirements for lambda2 in core functions other than the known functions in RNA capping, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Reovirus strains Type 1 Lang (T1L) and T3D were our laboratory stocks, originally obtained from Dr. B. N. Fields. Rabbit polyclonal antiserum and purified polyclonal antibodies specific for NS or 3 have been described previously (18,19). Monoclonal antibody (mAb) HA.11 specific for influenza virus hemagglutinin (HA) epitope was obtained from Covance Research Products, and rabbit polyclonal antibody specific for the HA epitope was obtained from Zymed Laboratories Inc. mAb DO-1 specific for p53 (Santa Cruz Biotechnology) was a generous gift from Dr. D. M. Knipe (Harvard Medical School).…”
Section: Methodsmentioning
confidence: 99%
“…Reovirus strains Type 1 Lang (T1L) and T3D were our laboratory stocks, originally obtained from Dr. B. N. Fields. Rabbit polyclonal antiserum and purified polyclonal antibodies specific for NS or 3 have been described previously (18,19). Monoclonal antibody (mAb) HA.11 specific for influenza virus hemagglutinin (HA) epitope was obtained from Covance Research Products, and rabbit polyclonal antibody specific for the HA epitope was obtained from Zymed Laboratories Inc. mAb DO-1 specific for p53 (Santa Cruz Biotechnology) was a generous gift from Dr. D. M. Knipe (Harvard Medical School).…”
Section: Methodsmentioning
confidence: 99%
“…4a-c). This region of λ1 has been identified as an opening to a small channel through the shell 47,48 (Figs. 4a,c and 6).…”
Section: Orientation Of λ3 and Route Of Transcript Exitmentioning
confidence: 99%
“…13 In addition, research undertaken on mammalian reovirus, another member of the Reoviridae family, has demonstrated that removal of the pentonal l2 protein results in complete loss of RNA transcriptase activity. 27 Taken together, these observations suggest that the reduced occupancy of VP6 trimers at the 5-fold vertices may lead to the diminished yield of RNA from transcribing Wa DLPs.…”
Section: Absence Of Pentonal Vp6 Trimers In Human Wa Dlp and The Funcmentioning
confidence: 94%